Pengaruh Waktu Dan Sudut Penyemprotan Pada Proses Sand Blasting Terhadap Laju Korosi Hasil Pengecatan Baja AISI 430 - Sulistyo, Erwin; Setyorini, Putu Hadi (Rekayasa Mesin, 2011)
The purpose of this study was to determine the influence of time and spraying angle on the process of sand blasting on the rate of corrosion of AISI 430 painting. Research conducted by the method of experimental research. Parameters in the sand blasting process used was the time of spraying with a variation of 35 seconds, 55 seconds, 75 seconds and 95 seconds and spray angle with the variation of 60 °, 75 ° and 90 °. This type of paint used paint is NC (Nitrocellulose) with electrostatic spray method. Corrosion test carried out by using a wet corrosioncell. Result showed that the angle and time of spraying have an influence on the corrosion rate.The lowest corrosion rate occurs at an angle of 90 ° spraying and spraying time of 35 seconds with the corrosion rate (milli inch / year) 1.72813E-06, whereas the highest corrosion rate occurred at an angle of 60 ° and spraying time 95 seconds with a corrosion rate (mils/year)0.00020454.Keywords: sand blasting, corrosion